Determination of fetal sex in cattle by cytologic examination of amniotic fluid - Bongso, Tuan Ariffeen; Wettimuny, S. G. de S; Edirisinghe, R.; Kumaratileke, L. (American Veterinary Medical Association, 1978)

(untitled)
Amniotic fluid smears of bovine fetuses (69 males and 65 females) at various stages of gestation were stained by the Papanicolaou method. Percentage counts of eosinophilic, orangeophilic and cyanophilic cells were determined by examining 500 cells per sample. The cyanophilic cell count was significantly (P < 0.001) higher for the females (37% .+-. 3% to 47% .+-. 3%) than for the males (19% .+-. 2% to 32% .+-. 3%). Significant differences were not recorded with the eosinophilic and the orangeophilic cell counts. The percentage cyanophilic count could therefore be used as a method of prenatal sex determination